2021
DOI: 10.1001/jamanetworkopen.2021.0422
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Withdrawal Rates in Hospitalized Patients During the COVID-19 Pandemic

Abstract: The association of the COVID-19 pandemic with AUD and AW has been much debated. 5 This cohort study found an overall increase in AW rates in 2020, with a peak at the end of the stay-at-home order. Moreover, increased AW rates continued during the reopening phases. It is not clear why IRRs were higher in 2020 before the stay-at-home orders. Although the use of the revised Clinical Institute Withdrawal Assessment for Alcohol to identify AW limits the false-positive rate, it may underestimate the true AW rate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 6 publications
(8 reference statements)
1
27
0
Order By: Relevance
“…This marked change is likely associated with recent patterns in high-risk alcohol use. 1 , 2 Additional contributions may have included transplant centers’ increasing acceptance of pursuing liver transplantation for acute alcohol-associated hepatitis 3 and a revision of the liver transplantation allocation system in February 2020, 5 as well as possibly concurrent lifestyle changes and COVID-19 infection itself. Nevertheless, these recent recipients of liver transplant will require intensive longitudinal multidisciplinary care to reduce their risk of alcohol relapse and ensure successful outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This marked change is likely associated with recent patterns in high-risk alcohol use. 1 , 2 Additional contributions may have included transplant centers’ increasing acceptance of pursuing liver transplantation for acute alcohol-associated hepatitis 3 and a revision of the liver transplantation allocation system in February 2020, 5 as well as possibly concurrent lifestyle changes and COVID-19 infection itself. Nevertheless, these recent recipients of liver transplant will require intensive longitudinal multidisciplinary care to reduce their risk of alcohol relapse and ensure successful outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… Sharma et al. (2021) [10] Alcohol-related hospitalizations Retrospective Cohort Hospitalizations for alcohol withdrawal at a tertiary hospital in Delaware ( N = 847) 34% increase in hospitalizations for alcohol withdrawal at the end of stay-at-home orders in 2020 compared to 2019. White et al.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol withdrawal in the ED has been associated with increased use of critical care resources [9], and frequent ED visits for alcoholrelated presentations have been associated with high relative mortality rates [1,10]. Furthermore, recent studies have demonstrated significant increases in the proportion of alcohol withdrawal-related ED visits during the COVID-19 pandemic, highlighting the rapidly growing burden of alcohol use on EDs across the world [11][12][13][14].…”
mentioning
confidence: 99%